Cost-effectiveness of focal psychodynamic therapy and enhanced cognitive–behavioural therapy in out-patients with anorexia nervosa. Issue 16 (9th September 2016) - Egger, N.; Wild, B.; Zipfel, S.; Junne, F.; Konnopka, A.; Schmidt, U.; de Zwaan, M.; Herpertz, S.; Zeeck, A.; Löwe, B.; von Wietersheim, J.; Tagay, S.; et al.
Abstract : Background: Anorexia nervosa (AN) is a serious illness leading to substantial morbidity and mortality. The treatment of AN very often is protracted; repeated hospitalizations and lost productivity generate substantial economic costs in the health care system. Therefore, this study aimed to determine the differential cost-effectiveness of out-patient focal psychodynamic psychotherapy (FPT), enhanced cognitive–behavioural therapy (CBT-E), and optimized treatment as usual (TAU-O) in the treatment of adult women with AN. Method: The analysis was conducted alongside the randomized controlled Anorexia Nervosa Treatment of OutPatients (ANTOP) study. Cost-effectiveness was determined using direct costs per recovery at 22 months post-randomization ( n = 156). Unadjusted incremental cost-effectiveness ratios (ICERs) were calculated. To derive cost-effectiveness acceptability curves (CEACs) adjusted net-benefit regressions were applied assuming different values for the maximum willingness to pay (WTP) per additional recovery. Cost–utility and assumptions underlying the base case were investigated in exploratory analyses. Results: Costs of in-patient treatment and the percentage of patients who required in-patient treatment were considerably lower in both intervention groups. The unadjusted ICERs indicated FPT and CBT-E to be dominant compared with TAU-O. Moreover, FPT was dominant compared with CBT-E. CEACs showed that the probability for cost-effectiveness of FTP compared with TAU-O and CBT-E was ⩾95% if the WTP per recovery was ⩾€9825 and ⩾€24 550, respectively. Comparing CBT-E with TAU-O, the probability of being cost-effective remained <90% for all WTPs. The exploratory analyses showed similar but less pronounced trends. Conclusions: Depending on the WTP, FPT proved cost-effective in the treatment of adult AN.